The Kennedys in the world : how Jack, Bobby, and Ted remade America's empire - Haas, Lawrence J. (Potomac Books, An imprint of the University of Nebraska Press, 2021)
Lawrence J. Haas explores how the Kennedy brothers reshaped America's empire for more than six decades after World War II.